2011
DOI: 10.1371/journal.pone.0021650
|View full text |Cite
|
Sign up to set email alerts
|

TMPRSS2/ERG Promotes Epithelial to Mesenchymal Transition through the ZEB1/ZEB2 Axis in a Prostate Cancer Model

Abstract: Prostate cancer is the most common non-dermatologic malignancy in men in the Western world. Recently, a frequent chromosomal aberration fusing androgen regulated TMPRSS2 promoter and the ERG gene (TMPRSS2/ERG) was discovered in prostate cancer. Several studies demonstrated cooperation between TMPRSS2/ERG and other defective pathways in cancer progression. However, the unveiling of more specific pathways in which TMPRSS2/ERG takes part, requires further investigation. Using immortalized prostate epithelial cell… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
80
0
1

Year Published

2012
2012
2018
2018

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 100 publications
(85 citation statements)
references
References 43 publications
(71 reference statements)
3
80
0
1
Order By: Relevance
“…Many other pathways that converge with the AR regulate EMT in CRPC, including the growth factor receptor tyrosine kinase (RTK), PTEN, notch, hedgehog, Wnt, and TMPRSS2:ERG pathways (Leshem et al 2011) and the STAT3 pathway (Karhadkar et al 2004, Acevedo et al 2007, Bisson & Prowse 2009, Mulholland et al 2012. For example, in a study by Izumi et al, the silencing of AR in LNCaP cells and PCa mouse xenograft models was shown to promote cell migration by up-regulating the CCL2-dependent STAT3 and EMT pathways.…”
Section: Ar As a Regulator Of Emtmentioning
confidence: 99%
“…Many other pathways that converge with the AR regulate EMT in CRPC, including the growth factor receptor tyrosine kinase (RTK), PTEN, notch, hedgehog, Wnt, and TMPRSS2:ERG pathways (Leshem et al 2011) and the STAT3 pathway (Karhadkar et al 2004, Acevedo et al 2007, Bisson & Prowse 2009, Mulholland et al 2012. For example, in a study by Izumi et al, the silencing of AR in LNCaP cells and PCa mouse xenograft models was shown to promote cell migration by up-regulating the CCL2-dependent STAT3 and EMT pathways.…”
Section: Ar As a Regulator Of Emtmentioning
confidence: 99%
“…Several strides have been carried out to identify the factors contributing to EMT in PCa. Transforming growth factor beta (Zhu & Kyprianou 2010), nicotinamide adenine dinucleotide-dependent histone deacetylase or SIRT1 (Byles et al 2012), platelet-derived growth factor (Kong et al 2009), TMPRSS2/ERG (Leshem et al 2011), SNAI2 (SLUG) (Emadi Baygi et al 2010), DAB2IP (Xie et al 2010), Hsp27 (HSPB1) (Shiota et al 2013), and miRNAs (Ru et al 2012) have all been identified as EMT regulators in PCa. Interestingly, the majority of these factors mediate EMT via zinc finger E-box-binding protein (ZEB) family members, such as ZEB1 (dEF1 or AREB6) and ZEB2 (Smad-interacting protein 1 (SIP1)) (Gregory et al 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Recent work, however, failed to confirm that TMPRSS2:ERG correlates with adverse tumor characteristics and unfavorable prognosis (10,11). Nonetheless, this fusion is a likely initiating event in prostate cancer development representing a separate etiology with unique expression and epigenetic profiles (12)(13)(14).…”
Section: Introductionmentioning
confidence: 99%